A Trust-based Defence Scheme for Mitigating Blackhole and Selective Forwarding Attacks in the RPL Routing Protocol - Airehrour, David; Guttierrez, Jairo; Ray, Sayan Kumar (Journal of Telecommunications and the Digital Economy, 2018)
The routing protocol for low-power and lossy networks (RPL) has gained prominence as the standard IoT routing protocol. However, it faces like many other routing protocols diverse attacks. Many studies have been proposed to secure the RPL protocol, and simulation studies have been put forward as the main research method, while testbed experiments, though an authentic research and testing method, have been ignored. Although testbed experiments and simulation studies have their strengths and limitations, testbed techniques could be used as a verifiable validation method for simulation studies. This study is a follow up research work to validate our simulation study, which addressed Blackhole attacks in the RPL routing protocol. In addition, Selective Forwarding attacks are also addressed. It implements a testbed while embedding our Trust-based RPL protocol and the standard RPL protocol in a smart environment configuration. Based on the test experiments, we provide a proof-of-concept of the validity of our claim that our Trust-based RPL protocol provides a comprehensive defence (simulation and testbed) against Blackhole and Selective Forwarding attacks.